Assessing the Effectiveness of the Electrocardiography Method in Diagnosing Cardiovascular Diseases in Infants - Khalilov Otabek Nematillaevich (Scholars Digest Publishing, 2023)
This article evaluates the utility and effectiveness of electrocardiography (ECG) in the diagnosis of cardiovascular disease in infants. The aim is to evaluate the role of ECG as a diagnostic tool, especially in the early detection and accurate diagnosis of cardiac disease in pediatric patients. The study includes literature analysis, methods, results, discussion, conclusions and suggestions to provide a comprehensive overview of the topic.
Keywords: Electrocardiography, cardiovascular diseases, infants, diagnostics, pediatric cardiology.